Counting Teller Quantity for Better Queue in Financial Institution: Case of Bank Central Asia, Metro Indah Mall Branch Office-Bandung - Cut Irna Setiawati; Farah Atsila Budyanna (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2017)
A queue is frequently encountered in financial transaction at the bank. The similar thing also occurs at Bank Central Asia (BCA), Bandung. BCA Bank actually has SOP stating that it allocates 5 minutes for financial service at the teller. This research aims to precisely determine the total calculation of teller at BCA Bank. Research methodology uses a quantitative method and it encompasses the descriptive research where the operational variable functioned is a multichannel-single phase (M/M/S). There is more than one teller operating and there is only one service phase that must be passed by the customers to finish the transaction. The results showed that each teller could serve 10 persons per hour and teller busy level is 97%. The average time spent by each customer in the system is 63 minutes and in the queue line is 57 minutes. This research results showed that there should be 7 tellers to get an optimal result, meaning that BCA Bank should provide three more tellers per day. Providing more tellers will indicate better benefits for the customer.